The pathogen biology, identification and management of Rhizoctonia species with emphasis on isolates infecting turfgrasses - BIMAL S. AMARADASA, DILIP LAKSHMAN* and (Indian Phytopathology, 2014)
Rhizoctonia solani is an economically important soilborne basidiomycetous pathogen of worldwide distribution and it is known to attack at least 188 species of higher plants, including crops, vegetables, ornamentals, forest trees and turfgrasses. The pathogenic isolates may belong to multiple genera and species (i.e., Thanatephorus spp., Waitea spp., Ceratobasidium spp., etc.) and are variously responsible for pre- or post-emergence damping off of seedlings, crown necrosis and root rots, aerial blights and wilts, fruit rots and post-harvest losses, accounting for 5-10% loss in yield and product quality. Many non-pathogenic isolates of R. solani are decomposers of soil organic matter, contributors of soil ecology, symbiotic on plants and may serve as biocontrol agents. Isolates of R. solani are morphologically grouped based on the number of nuclei per cell and by hyphal anastomosis reactions, which are often unreliable methods for precise pathogen detection. Recent approaches utilizing molecular markers, genome finger printing, and ITS sequencing have increased the speed, precision, and practicality of accurately identifying or grouping R. solani isolates. Current investigations on endogenous double-stranded RNAs in relation to virulence and hypovirulence of R. solani and investigations at the ‘omics’ levels have opened up exciting possibilities for understanding its dynamic biological and pathogenic processes and interactions with environmental factors. This review will discuss modern approaches along with their potentials and limitations for investigating this challenging group of plant pathogens, with special reference to isolates pathogenic to turfgrasses.